Stakeholder perspectives of leadership in organisations within the New Zealand sport sector - Vulinovich, Katie (Auckland University of Technology, 2016)
To date, mainstream ‘traditional’ leadership research has concentrated on a leader-centred approach, assuming leader behaviour and abilities as the focal point, and, as a result overlooking the idea that everyone can enact and contribute to leadership. Typically these studies are situated within the business sector and have employed quantitative research methods focussing on the overt ‘leader’ with little recognition of stakeholder perspectives and the importance of context (Kihl, Leberman & Schull, 2010; Jackson & Parry, 2011). It is in more recent years that some scholars have begun to embrace a more all-encompassing view of leadership centring instead on the ‘informal’ ‘leadership’ view as opposed to the ‘formal’ ‘leader’ outlook (Jackson & Parry, 2011; Welty Peachey, Zhou, Damon & Burton, 2015). To contribute to this evolving body of leadership literature, predominantly that within the context of sport, this study sought to explore stakeholder perspectives of leadership in organisations within the New Zealand sport sector. More specifically, this overall aim was explored through the use of two guiding sub-questions: 1) what are selected individual stakeholder perspectives of leadership; and 2) what themes emerge from these perspectives that advance knowledge and understanding of leadership in the New Zealand sport sector? The social constructionist lens, viewing leadership as a relational, shared experience was adopted, also recognising the significant role context plays in leadership interactions (Foldy, Goldman & Ospina, 2008; Grint, 2005; Ospina & Schall, 2001). This social approach to understanding leadership coupled with the collaborative nature of sport itself and the lack of research in this area, validates the need to consider stakeholder perspectives of leadership within the sector. In order to gather this industry knowledge, a qualitative study was conducted incorporating a case study approach. Data were gathered from three individual stakeholders through semi-structured in-depth interviews resulting in rich, insightful sharing’s. These interviews revealed that among other leadership learnings such as the importance of developing people, understanding followers and building teams, the key emergent ideas are the importance of; self-awareness and emotional intelligence, developing and managing relationships, and the social, relational viewpoint of leadership. Overall this knowledge helps us to better understand the notion of leadership as a social, shared experience and contributes to enhancing our understanding of stakeholder perspectives of leadership within the New Zealand sport industry. In turn, these insights can be used to inform curriculum development of the leadership teachings in the Bachelor of Sport and Recreation at Auckland University of Technology, and help to enhance the development of students/graduates and their capabilities.
Keywords: Sport; Leadership; Stakeholder; Social construction; Case study; Qualitative